Neonatal AKI profile using KDIGO guidelines: A cohort study in tertiary care hospital ICU of Lahore, Pakistan - Rafia Gul; Zahid Anwar; Mehmood Sheikh; Ayesha Salamat; Samer Iqbal; Furqan Saleem; Samer Fatima (Frontiers Media S.A., 2022)
Background and objectiveAcute kidney injury (AKI) was observed in sick neonates and was associated with poor outcomes. Our cohort represents the neonatal characteristics of those diagnosed with AKI using Kidney Disease: Improved Global Outcome (KDIGO) guidelines.MethodologyA cohort study was conducted in the NICU of FMH from June 2019 to May 2021. Data were collected on a proforma. All continuous variables were not normally distributed and expressed as the median and interquartile range. Categorical variables were analyzed by proportional differences with the Pearson chi-square test or Fisher's exact tests. A multinomial logistic regression model was used to explore the independent risk factors for AKI. Time to the event (death) and the cohort's survival curves were plotted using the Cox proportional hazard model.ResultsAKI occurred in 473 (37.6%) neonates. The risk factors of AKI were outborn birth [adjusted odds ratio (AOR): 3.987, 95% confidence interval (CI): 2.564-6.200, p: 0.000], birth asphyxia (AOR: 3.567, 95% CI: 2.093-6.080, p: 0.000), inotropic agent (AOR: 2.060, 95% CI: 1.436-2.957, p: 0.000), antenatal steroids (AOR: 1.721, 95% CI: 1.213-2.443, p: 0.002), central lines (AOR: 1.630, 95% CI: 1.155-2.298, p: 0.005) and intraventricular hemorrhage (IVH)/intracranial hemorrhage/disseminated intravascular coagulopathy (AOR: 1.580, 95% CI: 1.119-2.231, p: 0.009). AKI significantly increases the duration of stay and mortality rates by 16.5% vs. 3.9% in neonates with normal renal function (p < 0.001).ConclusionAbout one-third of critically sick neonates had AKI. Significant risk factors for AKI were outborn birth, asphyxia inotropic agents, necrotizing enterocolitis, antenatal steroids central lines, and IVH. AKI is associated with an increased length of stay and increased mortality.